Could the study of ancient human remains help the modern clinic? Interpreting multiple osteomas, a difficult challenge - Licata, Marta; Tonina, Enrica; Ciliberti, Rosella; Fusco, Roberta; Tesi, Chiara; Larentis, Omar (Medicina Historica, 2022)
Some pathological features may be underestimate in clinical literature, especially the asymptomatic ones. This is the case of multiple osteomas, benign and primary bone tumors.  As a matter of fact, nowadays their incidence is 2-3% of bone tumour cases. Conversely, their prevalence in the archaeological sample seems to be greater.We describe three medieval subjects from Caravate (Varese), showing cases of multiple osteomas. From these cases, our interest arose towards the relationship between prevalence and incidence of multiple osteomas. Sex determination and age estimation were performed with the standard anthropological methods, pathological features with both, clinical and paleopathological literature.We diagnosed the condition of multiple osteoma, proposing all possible pathologies related to the development of multiple osteomas. This work, in which we briefly present the state of the art of our knowledge, is a starting point for a broader reflection on this issue.